2021
DOI: 10.1186/s12889-021-11169-x
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptability of self-testing for hepatitis C virus infection among the general population in the Nile Delta region of Egypt

Abstract: Background Self-testing for hepatitis C virus antibodies (HCVST) may be an additional strategy to expand access to hepatitis C virus (HCV) testing and support elimination efforts. We conducted a study to assess the usability and acceptability of HCVST among the general population in a semi-rural, high-HCV prevalence region in Egypt. Methods An observational study was conducted in two hospitals in the Nile Delta region. A trained provider gave an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
25
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 25 publications
8
25
2
Order By: Relevance
“…Just over half of 100 self-testers were able to complete all steps of the HCV self-test, and almost all interpreted the results correctly (most without assistance). We found the most frequently observed difficulties related to sliding the tube into the stand and removing the cap from the test tube, consistent with studies in Egypt ( 21 ) and Vietnam ( 20 ). We also found that the steps at which errors were observed differed slightly between the studies in China, Egypt ( 21 ) and Vietnam ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Just over half of 100 self-testers were able to complete all steps of the HCV self-test, and almost all interpreted the results correctly (most without assistance). We found the most frequently observed difficulties related to sliding the tube into the stand and removing the cap from the test tube, consistent with studies in Egypt ( 21 ) and Vietnam ( 20 ). We also found that the steps at which errors were observed differed slightly between the studies in China, Egypt ( 21 ) and Vietnam ( 20 ).…”
Section: Discussionsupporting
confidence: 90%
“…This study expands the literature by examining the usability, feasibility, and acceptability of HCV self-testing in China. Similar pilot studies on HCV self-testing have been conducted by the FIND and WHO team in different settings and populations in Vietnam ( 20 ), Egypt ( 21 ), Kenya ( 22 ) and Georgia. Findings from this study provide insights for the implementation of HCV self-testing programmes and research among MSM.…”
Section: Discussionmentioning
confidence: 83%
“…Further research is still needed on the usability and acceptability of HCVST in different populations and geographic regions to inform policy recommendations. To address this gap, FIND in collaboration with WHO has conducted a series of usability and acceptability studies among different populations in China, Egypt [ 31 ], Kenya, Malaysia, Rwanda, Pakistan and Vietnam [ 32 ]. In this study in Georgia, we sought to assess the usability and acceptability of oral-based HCVST among PWID and MSM/transgender people (TG).…”
Section: Introductionmentioning
confidence: 99%
“…Rapid tests that are performed within health facilities staffed by health professionals are POC tests, which permit rapid diagnosis and treatment or entry into care in a single visit (54). Self-testing strategies which remove the requirement to undergo POC testing at a healthcare facility have been assessed in LMIC regions and have shown advantages of ease of use, convenience, and privacy; however, provision of testing instructions, at the point of sale (pharmacy or hospital) is likely required to minimize confusion and ensure the procedure is followed correctly (55,56). The major limitations of most POC tests in LMIC involve procurement, distribution and handling of POC tests, training of personnel, and regulatory protocols which may hinder access in certain LMIC (32).…”
Section: Rapid Point Of Care Diagnostic Testingmentioning
confidence: 99%